MØDER OG GRÆNSER – TVÆRKUNSTNERISKE PLANER FOR BYENS HAVN. EN SØNDERBORG-HISTORIE - Reeh, Henrik (K&K - Kultur og Klasse, 2010)
ENCOUNTERS AND BOUNDARIES. INTERARTISTIC PROJECTS FOR THE CITY’S HARBOUR. A SØNDERBORG STORY In the early 2000s, The Danish Arts Foundation strengthened a burgeoning interdisciplinary tendency in urban planning when it decided to fund strategic design projects for post-industrial Danish harbour cities. The present study delves into this process, which involved a specially composed team of seven members (architects, artists, and a scholar of cultural theory [the author of the present article]), as well as administrative and political institutions in Sønderborg, a historical city of 30,000 inhabitants in Southern Jutland, not far from Germany. Referring to French philosopher Michel de Certeau’s critical demonstration of a gap separating the urban planner from the very life of the city for which his plan or design is destined, the Arts Foundation team systematically attempted to reflect upon its own points of view as well as those of the citizens and society of Sønderborg. Notably, the design team explored the itineraries of everyday life as a basis for new urban spaces, architectural structures and pedestrian infrastructures, the aim being to reuse industrial urban elements of the early 20th century – elements that could easily be appropriated by the scale and practices of contemporary urban life. “Encountering the City’s Harbour”: these words summarise the concept underlying the urban design and development strategy proposed by the Arts Foundation team. A model comprising four levels – [1] studies from afar; [2] in situ explorations of the urban fabric; [3] elaboration of a key concept; [4] dialogues with urban users – systematises the collaborative efforts made from 2002 to 2005 and provides a practical answer to the structural challenge outlined by Certeau.